2016
DOI: 10.1371/journal.pone.0146085
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Spatial Association between Social Deprivation and Cardiovascular Disease Mortality at the Neighborhood Level

Abstract: Cardiovascular disease (CVD), the leading cause of death in the United States, is impacted by neighborhood-level factors including social deprivation. To measure the association between social deprivation and CVD mortality in Harris County, Texas, global (Ordinary Least Squares (OLS) and local (Geographically Weighted Regression (GWR)) models were built. The models explored the spatial variation in the relationship at a census-tract level while controlling for age, income by race, and education. A significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
7
24
0
1
Order By: Relevance
“…Former studies applying GWR on hypertension also found that the association between socio-economic status and hypertension depends largely on the place of residence [ 65 ]. Similar findings were reported for the association between cardiovascular disease and area deprivation [ 60 ]. Our results correspond well to these findings, showing that area deprivation is a significant predictor only in a part of the study area.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Former studies applying GWR on hypertension also found that the association between socio-economic status and hypertension depends largely on the place of residence [ 65 ]. Similar findings were reported for the association between cardiovascular disease and area deprivation [ 60 ]. Our results correspond well to these findings, showing that area deprivation is a significant predictor only in a part of the study area.…”
Section: Discussionsupporting
confidence: 89%
“…Although the proportion of insurants aged 65 and older was significant in almost the entire study area, the strongest associations could also be observed in more deprived areas. The finding that demographic variables display a stronger association to chronic diseases in areas with higher deprivation is supported by previous findings for cardiovascular disease mortality [ 60 ] and highlights the use of GWR to analyze location-specific correlations between chronic conditions, demographic variables and area deprivation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Additionally, living in a healthy place can affect different subpopulations in different ways (26). For example, modification of CVD risk factors may have less effect among those with diagnosed or advanced CVD when compared with those who are yet undiagnosed and have modifiable risk factors, such as obesity or inactivity (27). The different relationship between neighborhood-level food access and premature CVD mortality in the 2 series of models presented here supports the importance of examining how the characteristics of a place might have different effects on the health of the population living there.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the socio-demographic patterns of hypertension prevalence in low-and-middle-income countries (LMIC) found that the prevalence of hypertension was associated with and varied by socio-demographic region [7]. Elsewhere, Ford and Highveld [8] have shown that geographic disparities in the distribution of certain cardiovascular morbidity have been observed and linked to socioeconomic deprivation; however, little is known about the geographic overlaps in these conditions. The overlapping epidemiology of the conditions may be better understood by pooling data across the conditions in a unified way [9].…”
Section: Introductionmentioning
confidence: 99%